Structural performance of beam system with T-stub type slit damper. (15th February 2020) - Park, Hae-Yong; Oh, Sang-Hoon
Highlights: A T-stub type slit damper (TSD) connection detail is proposed. The proposed detail can complement the shortcomings of existing relative details. Moment-resistance connection that satisfies special moment frames established. A beam system strength/beam damage relationship performance curve is derived. Derived performance curve facilitates appropriate design choices for applications. Abstract: In this study, the structural performance of a beam system with a beam-to-column connection-type damage-controlled system was investigated. First, a connection detail with improved geometry was proposed based on results obtained from previous studies. The proposed connection detail uses a horizontally arranged steel slit damper as an energy absorption device and consists of support elements to help the effective bending and shear behavior of the slit damper. The overall behavior characteristics are similar to the Simpson strong-tie connection; however, the energy absorption device of the proposed detail is installed only at the bottom of the beam, and the connector attached to the top of the beam functions as a rotational hinge. The strength formula of the beam system with a new connection detail was derived according to the mechanical behavior pattern. The stiffness formula of the beam system was proposed considering the geometric characteristics of the connection elements. For practical verification, a cyclic loading test was conducted on the beam-to-column connection with a T-stub type slit damper designed with appropriate strength. Nonlinear finite element analysis (FEA) was also conducted using the aspect ratio of the beam and damper strength as variables. The test and FEA results confirmed that the strength and stiffness of the beam system with the proposed connection detail exhibited responses similar to the predicted values. When the damper strength was designed to be lower than that of the beam, the deformation caused by the rotational behavior of the connection was concentrated on the damper according to the moment gradient generated in the flexural members. As the damper/beam yield strength ratio or rotation angle increased, the plasticity of the beam was found to gradually strengthen. A performance curve was derived from the relationship between the strength of the beam system and the damage to the beam according to the damper strength design conditions. It is expected that a moment-resisting frame that satisfies the requirements can be designed by applying this derived performance curve to low- and mid-rise steel buildings. Finally, the hysteretic model of the beam system with the proposed connection detail was developed through an approximation to a tri-linear model according to the design condition.